Pelayanan Informasi Kreatif pada Daya Tarik Wisata Alam Lembah Harau, Kabupaten Lima Puluh Kota - Trisna Putra; Waryono Waryono; Rian Surenda (Institut Pertanian Bogor, 2020)
Signage and destination map is one important information services provided by tourism destination management. Harau Valley is one of the potential tourism destinations in West Sumatra, however it provides less information service to its visitors. To meet the needs of the information services in Harau Valley, a program is held by having a method of community development practice. The approaches being used is participative and educative toward tourism care groups (kelompok sadar wisata). Through the program, the groups are able to make signage and destination maps. The signage was created by the group by using unused material. The outcome of the program shows success with the indications of the high enthusiasm of participants. Based on the finding the enthusiast of the participant is increased as the aspect of cognitive 90%, aspect affective 85%, and conative 95%.